An efficient system for incorporation of unnatural amino acids in response to the four-base codon AGGA in Escherichia coli - Lee, Byeong Sung; Kim, Suyeon; Ko, Byoung Joon; Yoo, Tae Hyeon (Biochimica et biophysica acta. General subjects, 2017)
Adding new amino acids to the set of building blocks for protein synthesis expands the scope of protein engineering, and orthogonal pairs of tRNA and aminoacyl-tRNA synthetase have been developed for incorporating unnatural amino acids (UAAs) into proteins. While diverse systems have been developed to incorporate UAAs in response to the amber codon, less research has been focused on four-base codons despites their advantages. In this study, we report an efficient method to incorporate UAA in response to an AGGA codon in Escherichia coli. The Methanococcus jannaschii tyrosyl-tRNA synthetase-tRNACUA(MjTyrRS-MjtRNACUA) orthogonal pair has been engineered to incorporate diverse UAAs in response to the amber codon. To apply the engineered MjTyrRS enzymes for UAAs to a four-base codon suppression, we developed an MjTyrRS-MjtRNAUCCU pair system that enabled incorporation of UAAs in response to the AGGA codon in E. coli. Using this system, we demonstrated that several UAAs could be incorporated quantitatively in the AGGA site. In addition, multiple AGGA codons were successfully suppressed in an E. coli strain when the endogenous tRNACCUArg gene was knocked out. An efficient system was developed for the incorporation of UAAs in response to the AGGA four-base codon in E. coli, and the method was successfully demonstrated for several UAAs and for multiple AGGA sites. The developed system can expand the repertoire of protein engineering tools based on amino acid analogues in combination with other UAA incorporation methods. This article is part of a Special Issue entitled "Biochemistry of Synthetic Biology - Recent Developments" Guest Editor: Dr. Ilka Heinemann and Dr. Patrick O’Donoghue. •A method for incorporation of unnatural amino acids in response to the AGGA codon is developed.•The method is based on an engineered orthogonal pair of aminoacyl-tRNA synthetase and tRNAUCCU.•The engineered tRNAUCCU improves the efficiency as well as the specificity of the method.•Knocking out a competitive tRNA gene of ArgW increases the AGGA suppression efficiency.•The method is demonstrated for several unnatural amino acids and for multiple AGGA sites.